Lead with your heart, hyper innovate, and make a difference - JOHANNS, Steve (Institutional Knowledge at Singapore Management University, 2021)
Steve Johanns, founder and former Chairman of Veriown Global, is now taking smart villages into Sub-Saharan Africa through his company Villedge Solutions. He talks about his entrepreneurial journey in the world of hyper innovation and the secrets found in last mile empowerment.